Statistical tools in solving the problems of managing the development of the territories - Vladimir Glinskiy; Liudmila Serga; Valentina Pulyaevskaya; Владимир Васильевич Глинский; Людмила Константиновна Серга; Валентина Леонидовна Пуляевская (Information and publishing center "Statistics of Russia", 2016)
In this publication are outlined the problems of using statistical indicators for information support of effective strategic management decisions at the municipal level. The system of indicators to measure the level of social and economic development of municipalities with emphasis to positive and destructive factors - «stimulants» and «deterrents» - was formed. Gross municipal product (GMP) calculation methods are reviewed, an algorithm for rapid assessment of gross municipal product by the factor estimates, which is based on the significant relationship of the gross municipal product and gross regional product in two versions: regression on significant indicators and regression on main factors. Classification of municipalities of the Republic of Sakha (Yakutia) for 2008-2012 was carried out in terms of social-and-economic development using the following algorithms: by the ideology of the multivariate median at regular intervals and cluster analysis by Ward’s method that made it possible to verify the obtained partitions. The authors studied social-and-economic situation of the municipalities of the Republic of Sakha (Yakutia), identified municipalities-leaders, providing a relatively higher quality of development of the regional economy, the «position» of each municipality in the economic space of the region was rated. Possibility for studying the development and operation patterns of the municipalities, as a relatively independent production-and-territorial units, on the basis of the gross municipal product was proved. Results of typological analysis indicate that there are significant disproportions in social-and-economic development between the industrial and agricultural municipalities of the region under review. Conclusions and recommendations were made, specifically, the need to assess economic performance of municipalities on a regular and systematic basis. Data from the state statistics for the Republic of Sakha (Yakutia) was used as an information base for this research. В работе рассматриваются ...